Peningkatan Hasil Belajar Peserta Didik Sekolah Dasar Melalui Model Pembelajaran Kooperatif Tipe Example Non Example - Lestari, Lestari; Rumtutuly, Fransheine (Sora Journal of Mathematics Education, 2024)
This study aims to improve mathematics learning outcomes at SD Negeri Wakarleli through the application of cooperative learning model type example non example. This research is a classroom action research conducted collaboratively between researchers and classroom teachers. The subjects in this study were grade VI students totaling 18 students. The research design used in this classroom action research is a design by Arikunto which is carried out in two cycles. The instruments used in this study, namely pre-test and post-test questions, observation sheets, interview guidelines, and documents. The data collection techniques used were tests, observations, documentation and interviews. The variables in this study consisted of math learning outcomes and the example non example learning model. The data were analyzed using qualitative descriptive method through the stages of reduction, data presentation, and conclusion drawing. The results showed that from the initial conditions before the action was taken, students had not optimally shown academic ability, experiencing significant changes, this was seen from the percentage of learning outcomes in cycle 1 of 55.56% increasing to 100% in cycle 2, so it can be concluded that the example non example learning model can improve math learning outcomes at SD Negeri Wakarleli.